Wireless communications : principles, theory and methodology - Zhang, Keith Q. T. (Chichester [England] : Wiley, 2016)
"Provides the reader with an overall picture of wireless communications, carefully expounds its technical details, not only covering a variety of main results and conclusions but also revealing the methodology used for their derivations"--
Mathematical background -- Channel characterization -- Digital modulation -- Minimum shift keying -- Channel coding -- Diversity techniques -- Processing strategies for wireless systems -- Channel equalization -- Channel decomposition techniques -- Turbo codes and turbo principle -- Multiple-access channels -- Wireless MIMO systems -- Cooperative communications -- Cognitive radio.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Wireless communication systems; TECHNOLOGY & ENGINEERING / Mobile & Wireless Communications; Wireless communication systems; Electronic books